Cose, oggetti e ultra-cose. Il contenuto della percezione tra fenomenologia e psicologia (Itinera, 2025)
Things, Objects and Ultra-Things The Content of Perception Between Phenomenology and PsychologyThis article explores the problem of perception and the paradoxes that characterize it from a phenomenological point of view. While the object always appears from a subjective standpoint, the thing as a total whole far exceeds the grasp of any single perspective. The issue of the transcendence of the perceived is thus analysed from Husserlian formulations up to the positions of Aron Gurwitsch and Maurice Merleau-Ponty. Both philosophers propose a revision of Husserlian phenomenology that frees it from the morphogenetic bias that still underpins it. By considering the content of perception as a form in the Gestalt sense, Gurwitsch and Merleau-Ponty appear to be able to rehabilitate the presence of the whole within each of its parts. However, while Gurwitsch situates this topic on an ideal and hypothetical level—with no real consequences for our concrete and perspectival experience—Merleau-Ponty takes it as a prompt to reconceive transcendence and generality as inseparable from their sensible unfolding. By transforming the concept of constitution into one of communion and by replacing the ideal of complete adequacy with that of perceptual evidence, Merleau-Ponty seeks to account for our concrete relationship with the object as a bodily correspondence to things against the active backdrop of a shared world. At first, the article explores Phenomenology of Perception and, in particular, the chapter The Thing and the Natural World, criticised by Gurwitsch. Then, the focus shifts to Merleau-Ponty’s Sorbonne lectures. The aim is to highlight a certain convergence between child perception and philosophical vision. Merleau-Ponty’s reference to the notion of ultra-chose, borrowed from Henri Wallon, and his later claim that “all things are ultra-things” is examined. Finally, the article explores possible connections between Merleau-Ponty’s theory of perception and Donald Winnicott’s studies on child development in order to emphasise a relationship of communion with objects and a personal horizon that arises precisely through full contact with things and people that inhabit one’s world.
Keywords: phenomenology; transcendence; ultra-things; object; psychoanalysis